Agency and Free Will in the Icelandic Sagas - Mayus, Melissa, 1983- (2013)
Much has been written about the conversion to Christianity as it took place in medieval Iceland and the way it is presented in the Icelandic sagas. Likewise, the topics of the conception of fate in Old Norse-Icelandic literature and the social structure which locked people into particular roles in medieval Iceland have been well documented. This thesis brings all three of these strands—religious attitudes toward free will, conceptions of fate, and social structures—together in order to gain a better understanding of how human agency is fostered or constrained in case studies from three different sagas. Thus this study first considers the passages most relevant to teachings on free will found in the Íslensk Hómilíubók in order to establish what types of religious ideas about free will were likely to have been in common enough circulation to affect the way saga authors portrayed free will in their works. It then turns to a brief survey of the secondary literature in order to understand the basic social principles that are illustrated in the sagas and the fatalistic tradition which also informed the sagas. From there, the thesis turns to particular case studies from three of the sagas in order to determine how these varying forces affected the saga authors’ portrayal of human agency and free will. The first example considered is Laxdæla saga, with a focus on the build-up and confrontation between the characters Bolli and Kjartan; this episode reveals how characters could have their agency severely curtailed just by social pressures with very little reference to religious teaching. The next case study, Njáls saga, offers a mix of ideas about agency. Njáls saga characters are somewhat affected by fate and religious concerns, but again are ultimately constrained largely by social pressure in the most prominent episodes. The final case study draws on Hrafns saga Sveinbjarnarsonar, which offers an understanding of agency that is much more steeped in religious teaching than the other examples. In this saga, the author ...